Polypharmacy and high-alert medications in patients with nasally placed feeding tube on admission and at hospital discharge: Multicenter cross-sectional study - Fernanda Raphael Escobar Gimenes; Juliana Santana de Freitas; Janine Koepp; Patrícia Rezende do Prado; Rochele Mosmann Menezes; Jacinthe Leclerc; Adriane Pinto de Medeiros; Thalyta Cardoso Alux Teixeira; Rhanna Emanuela Fontenele Lima de Carvalho; Maria Olívia Barboza Zanetti; Adriana Inocenti Miasso; Jennifer Midiani Gonella (Elsevier, 2024)
Background: Polypharmacy and the use of high-alert medications in patients with nasally placed feeding tube (NPFT) increase the risks of drug related problems. Objective: Characterize drugs prescribed to patients with NPFT and compare the rates of polypharmacy and high-alert medication use at admission and hospital discharge. Design and setting: Multicenter cross-sectional study with 327 participants. Methods: Data of patients with NPFT were obtained from the medical records and recorded in an electronic data collection tool. Mean number of drugs, polypharmacy and number of high-alert medications prescribed on admission and at discharge were compared using Wilcoxon or McNemar's tests. Generalized Estimating Equations analyzed the relationship between polypharmacy and high-alert medications according to age and time point. Primary reason for hospital admission, level of consciousness, severity of comorbid diseases and patient care complexity were also assessed. Results: Most patients were male, older people, hospitalized for circulatory system diseases and had at least one comorbidity. On admission, a significant number of patients were alert (59.9%), at high risk for death (43.1%) and high dependent on nursing care (35.4%). Additionally, 92% patients were on polypharmacy on admission, versus 84.7% at hospital discharge (p = 0,0011). The occurrence of polypharmacy was independent of age (p = 0.2377). >17% of all drugs prescribed were high-alert medications, with no statistically significant difference between admission and discharge (p = 0,3957). There was no statistical evidence that the use of high-alert medications increases with age (n = 0,5426). Conclusions: These results support the planning of multidisciplinary qualified actions for patients using NPFT.